RANCANG BANGUN APLIKASI TRACER STUDY BERBASIS WEB STUDI KASUS PADA FAKULTAS ILMU KOMPUTER UNIVERSITAS BUNG KARNO - Wahyu Alfarisi; Fauziyah Fauziyah; Bernadus Gunawan Sudarsono (LPPM Universitas Bina Bangsa, 2022)
Bung Karno University is a university located in central Jakarta. The Tracer Study Information System at Bung Karno University currently is in the process of distributing tracer study forms and filling out tracer study forms, they still have to come to campus, not to mention that in this pandemic era it is difficult to do which results in delays in the process of processing the results of tracer study data filled out by college student. and it takes time to return the completed tracer study form to the faculty. In defining requirements and analyzing and designing systems in order to achieve this, data collection methods are needed by means of literature study, observation, interviews, design, and testing. The result of writing this thesis will be the construction of a web-based tracer study information system which is expected to be able to experience the existing problems. The tracer study information system proposed for filling out the tracer study form has been systemized and can be directly received by students when the campus makes a filling schedule and makes it easier for students to fill in without having to take the tracer study form to campus, so that faculty can quickly receive tracer study forms that have been submitted. filled in by students. The Tracer Study Information System is expected to minimize the possibility of errors in making the results of the tracer study survey that has been carried out by the faculty